EVALUATION OF THE STABILITY OF A CRANE EQUIPPED WITH GROUND ANCHORS - I. S. Bychkov (Вестник СибАДИ, 2017)
Construction cranes are subject to a variety of external factors that affect stability and safety. Modern solutions do not provide sufficient stability and safety. To eliminate the threat from various factors, new support elements have been proposed. To assess the effect of soil anchors on the stability of a crane, a theoretical experiment was conducted, with various assumptions. The coefficient of cargo stability with ground anchors is determined and compared with the load stability factor with standard outriggers.